2012
DOI: 10.1242/jcs.118075
|View full text |Cite
|
Sign up to set email alerts
|

The endocannabinoid N-arachidonoyl glycine (NAGly) inhibits store-operated Ca2+ entry by abrogating STIM1/Orai1 interaction

Abstract: SummaryThe endocannabiniod anandamide (AEA) and its derivate N-arachidonoyl glycine (NAGly) have a broad spectrum of physiological effects, which are induced by both binding to receptors and receptor-independent modulations of ion channels and transporters. The impact of AEA and NAGly on store-operated Ca 2+ entry (SOCE), a ubiquitous Ca 2+ entry pathway regulating many cellular functions, is unknown. Here we show that NAGly, but not AEA reversibly hinders SOCE in a time-and concentration-dependent manner. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
(69 reference statements)
0
19
0
Order By: Relevance
“…Importantly, NAGly appears to have complex effects on different key ion transport systems expressed in endothelial cells. Recently we showed that in cells overexpressing the key molecular constituents of SOCE, the stromal interacting molecule 1 (STIM1) and the pore‐forming subunit of SOCE channels, Orai1, NAGly hampers SOCE primarily by uncoupling STIM1 from Orai1 (Deak et al ., ). Accordingly, that and our current data indicate that endogenous lipoaminoacid NAGly fine‐tunes the interplay between crucial molecular players of cellular signalling.…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, NAGly appears to have complex effects on different key ion transport systems expressed in endothelial cells. Recently we showed that in cells overexpressing the key molecular constituents of SOCE, the stromal interacting molecule 1 (STIM1) and the pore‐forming subunit of SOCE channels, Orai1, NAGly hampers SOCE primarily by uncoupling STIM1 from Orai1 (Deak et al ., ). Accordingly, that and our current data indicate that endogenous lipoaminoacid NAGly fine‐tunes the interplay between crucial molecular players of cellular signalling.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Bondarenko et al reported a previously unrecognized inhibitory effect of NAGly on plasma membrane Na 1 -Ca 21 exchange activity, which largely controls endothelial cell function [34]. NAGly has also been shown to reversibly hinder store-operated Ca 21 entry (a ubiquitous Ca 21 entry pathway regulating many cellular functions) in a time-and concentration-dependent manner [35]. These data unveiled an unknown inhibitory effect of NAGly on the signaling between stromal interacting molecule 1 (STIM1), a major contributor to Ca 21 signaling by means of its activity as Ca 21 channel regulator and Orai1 (a Ca 21 -selective ion pore).…”
Section: N-arachidonoyl Glycine and Related Glycinesmentioning
confidence: 99%
“…In a GPCR‐independent manner, anandamide and NAGly inhibit both forward and reverse modes of Na + ‐Ca 2+ exchanger in endothelial cells (Bondarenko et al ., ). In addition, NAGly was shown to directly potentiate the BK Ca channels (Bondarenko et al ., ) and inhibit store‐operated Ca 2+ entry in different cell types (Deak et al ., ). Because vascular signalling and function are chiefly regulated by Na + ‐Ca 2+ exchanger (Bondarenko, ; Andrikopoulos et al ., ), IK Ca , BK Ca (Vang et al ., ; Bondarenko et al ., ; Wulff and Kohler, ) and different members of TRP channels, identification of their contribution to GPCR‐dependent and ‐independent cannabinoid signalling still needs to be clarified.…”
Section: Gpcr‐independent Targets Of Cb Receptor Ligandsmentioning
confidence: 99%
“…However, in rat small mesenteric arteries, NAGly evoked a concentration‐dependent relaxation with an EC 50 value of 5.8 μM (Parmar and Ho, ), which is several orders higher than that required to activate GPR18. At these concentrations, NAGly exhibits a direct GPCR‐independent effect on a number of ion transport systems expressed in both endothelial and smooth muscle cells (Bondarenko et al ., ; Deak et al ., ). In endometrial cell line, HEC‐1B, THC was shown to be a full agonist for GPR18, with a calculated EC 50 value of 0.96 μM (McHugh et al ., ).…”
Section: Gpcr‐independent Targets Of Cb Receptor Ligandsmentioning
confidence: 99%